Global Inhibition of DC Priming Capacity in the Spleen of Self-Antigen Vaccinated Mice Requires IL-10 - Marvel, Douglas M.; Finn, Olivera J. (Frontiers in Immunology, 2014)
DC in the spleen are highly activated following intravenous vaccination with a foreign antigen, promoting expansion of effector T cells, but remain phenotypically and functionally immature after vaccination with a self-antigen. Up-regulation or suppression of expression of a cohort of pancreatic enzymes 24-72 hours post-vaccination can be used as a biomarker of stimulatory versus toleragenic DC, respectively. Here we show, using MUC1 transgenic mice (MUC1.Tg) and a vaccine based on the MUC1 peptide which these mice perceive as a self-antigen, that the difference in enzyme expression that predicts whether DC will promote immune response or immune tolerance, is seen as early as 4-8 hours following vaccination. We also identify early production of IL-10 as a predominant factor that both correlates with this early time point and controls DC function. Pre-treating mice with an antibody against the IL-10 receptor (IL-10R) prior to vaccination results in DC that up-regulate CD40, CD80, and CD86 and promote stronger IFNγ+ T cell responses. This study suggests that transient inhibition of IL-10 prior to vaccination could improve responses to cancer vaccines that utilize self-tumor antigens.